2019
DOI: 10.1103/physrevmaterials.3.103605
|View full text |Cite
|
Sign up to set email alerts
|

Discovery ofω-free high-temperature Ti-Ta-Xshape memory alloys from first-principles calculations

Abstract: The rapid degradation of the functional properties of many Ti-based alloys is due to the precipitation of the ω phase. In the conventional high-temperature shape memory alloy Ti-Ta the formation of this phase compromises completely the shape memory effect and high (> 100 • C) transformation temperatures cannot be mantained during cycling. A solution to this problem is the addition of other elements to form Ti-Ta-X alloys, which often modifies the transformation temperatures; due to the largely unexplored space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…The author listed as his future work that he will work on the development of models based on first-principle calculations for predicting the α" and ω phase [2] and indicated plans to study the effect of Sn addition in larger amounts in order to study its effect on the stability of the β phase [2]. Another work [16] based on shape memory alloys can also be compared with the present work. In their work [16], the authors performed first-principle calculations for developing ω-phase free Ti-Ta-X systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The author listed as his future work that he will work on the development of models based on first-principle calculations for predicting the α" and ω phase [2] and indicated plans to study the effect of Sn addition in larger amounts in order to study its effect on the stability of the β phase [2]. Another work [16] based on shape memory alloys can also be compared with the present work. In their work [16], the authors performed first-principle calculations for developing ω-phase free Ti-Ta-X systems.…”
Section: Discussionmentioning
confidence: 99%
“…Another work [16] based on shape memory alloys can also be compared with the present work. In their work [16], the authors performed first-principle calculations for developing ω-phase free Ti-Ta-X systems. Both of these references are thorough works and have included results from first-principle calculations [2,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The influence of oxidation on the martensitic transformation in the surface region was investigated [27]. Atomistic calculations on the stability of phases, especially the x-phase, were performed [28][29][30]. Special emphasis was placed on the role of the x-phase during functional fatigue of Ti-Ta alloys [31][32][33][34] and it has been shown that by controlling the temperature during heating and cooling one can counteract fast functional degradation by x-phase precipitation.…”
Section: Introductionmentioning
confidence: 99%